Antioxidant defense in rat brain regions after developmental lead exposure - Moreira, E. G.; Rosa, GJD; Barros, SBM; Vassilieff, V. S.; Vassillieff, I (Elsevier B.V., 2001)
Oxidative stress is considered a possible molecular mechanism involved in Pb neurotoxicity. Considering the vulnerability of the developing brain to Pb neurotoxicity, this study was carried out to investigate the effects of low-level developmental Pb exposure on brain regions antioxidant enzymes activities. Wister dams were exposed to 500 ppm of Pb, as Pb acetate, or to 660 ppm Na acetate in the drinking water during pregnancy and lactation. The activities of superoxide dismutase (SOD), glutathione peroxidase and glutathione reductase were determined in the hypothalamus, hippocampus and striatum of male pups at 23 (weaned) or 70 days (adult) of age. In the Pb-exposed 23-day-old pups, the activity of SOD was decreased in the hypothalamus. Regarding adults, there was no significant treatment effect in any of the enzymes and regions evaluated. Based on the present results, it seems that oxidative stress due to decreased antioxidant function may occur in weaned rats but it is suggested that this should not be the main mechanism involved in the neurotoxicity of low-level Pb exposure. (C) 2001 Elsevier B.V. Ireland Ltd. All rights reserved.
Keywords: lead; developmental lead exposure; antioxidant system; antioxidant enzymes